2002
DOI: 10.21273/jashs.127.6.901
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Growth and Development of the Strawberry Cultivars Elsanta, Bolero, and Everest

Abstract: The differences in growth and yield in the Junebearing strawberry (Fragaria ×ananassa Duch.) `Elsanta' and the everbearing `Bolero' and `Everest' were evaluated under field conditions. The seasonal patterns of radiation use efficiency and assimilate partitioning were also studied. Growth, development and yield showed considerable differences among cultivars. `Elsanta' showed the highest and `Bolero' and `Everest' the lowest values for almost all the vegetative parameters (lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…'Korona'. Riyaphan et al (2005) and Pérez- de-Camacaro et al (2002) found that the number of inflorescences plant -1 significantly varied in strawberry cultivars, which are in close conformity with the present findings. They also observed that the early flowering germplasm produced less number of trusses as well as flowers plant -1 compared to late flowering germplasm.…”
Section: Reproductive Characterssupporting
confidence: 92%
See 1 more Smart Citation
“…'Korona'. Riyaphan et al (2005) and Pérez- de-Camacaro et al (2002) found that the number of inflorescences plant -1 significantly varied in strawberry cultivars, which are in close conformity with the present findings. They also observed that the early flowering germplasm produced less number of trusses as well as flowers plant -1 compared to late flowering germplasm.…”
Section: Reproductive Characterssupporting
confidence: 92%
“…The variation in different germplasm as recorded might be due to genetic makeup. This result is in confirmatory with the findings of Pérez- de-Camacaro et al (2002). They found a significant difference in number of runner and crown plant -1 among the strawberry cultivars in UK.…”
Section: Qualitative Growth Characterssupporting
confidence: 91%
“…Commonly for polycarpic perennial plants, floral initiation happens once a year (‘seasonal flowering’, SF). However, some perennials have the ability to flower more than once, thereby prolonging a favourable season, through a process called ‘remontancy’ or ‘perpetual flowering’ (PF) (Albani and Coupland, ; de Camacaro et al ., ). The promise of enhancing fruit production by increasing the flowering period makes this trait a key objective of numerous breeding programmes.…”
Section: Introductionmentioning
confidence: 97%
“…Leaf production was nearly linear over 120 days in Wisconsin, with a leaf produced every six to thirteen days [55]. Leaf production was linear over 64 days in one cultivar in the United Kingdom and linear over 96 days in two cultivars [56]. A leaf was produced every two to five days during the main period of growth.…”
Section: Discussionmentioning
confidence: 99%